IMPROVING THE SPORTS TRAINING OF STUDENTS AT OLYMPIC AND PARALYMPIC SPORTS TRAINING CENTERS THROUGH THE USE OF NON-STANDARD EQUIPMENT (Bulletin of Innovative Research, 2026)
This article discusses enhancing the athletic training of students in Olympic and Paralympic sports training centers by utilizing non-standard equipment and tools. A pedagogical experiment was conducted with 12–15-year-old Greco-Roman wrestlers, where the experimental group’s training incorporated various non-traditional apparatus (self-made devices, technological innovations, and alternative training equipment) alongside the standard program. The control group followed conventional training methods. The findings revealed that the use of non-standard equipment led to significant improvements in the experimental group’s physical fitness levels and technical performance compared to the control group. Specifically, the experimental group demonstrated greater gains in strength, endurance, and agility tests, indicating the effectiveness of integrating unconventional training tools. Moreover, the creative training approach increased the students’ engagement and interest in the training process, which can further accelerate skill acquisition. These results underscore that incorporating innovative and non-standard equipment in training can be a valuable strategy for developing young athletes’ capabilities in both Olympic and Paralympic sports.